Experimental and Numerical Bending Analysis of Steel/Resin-Talk Sandwich Material - Pratama Arianto; Achmad Zubaydi; Bambang Piscesa; Tuswan Tuswan (IPTEK The Journal for Technology and Science, 2019)
Sandwich material can be used as the substitute for the ship conventional material. The core sandwich material used in this study consisted of a talk-resin-catalyst. The core mixture proportion is 90% resin and 10% talk. A thick steel plates is used as the face of the core sandwich material. Both experimental and numerical simulations are carried out to investigate the bending or flexural behavior of the proposed sandwich material. Three-point bending test has been carried out to determine the yield stress and maximum stress as well as the damage mechanism of the specimen up-to failure. From the investigation, the first failure process occurred at the mid-span as flexural cracks. As the load continue, these flexural cracks progressed until fully fracture of the core material take places. From the experimental investigation, it was found that the yield stress and maximum stress of the sandwich panel are 22.88 MPa and 28.63 MPa. On the other hand, numerical simulation is carried out using ABAQUS which has shown to be sufficient to predict the response of the sandwich-panel. However, a more sophisticated constitutive model is required to successfully model the experimental behavior in close agreement.